Visualyzart Project – The role in education - Barbas, Maria Potes (2018)
The VisualYzARt project intends to develop research on mobile platforms, web and social scenarios in order to bring augmented reality and natural interaction for the general public, aiming to study and validate the adequacy of YVision platform in various fields of activity such as digital arts, design, education, culture and leisure. The VisualYzARt project members analysed the components available in YVision platform and are defining new ones that allow the creation of applications to a chosen activity, effectively adding a new language to the domain YVision. In this paper we will present the role of the InstitutoPolitécnico de Santarém which falls into the field of education.